Avoiding Patient Harm With Parenteral Nutrition During Electrolyte Shortages. (December 2018) - Brown, Eric W.; McClellan, Nicole H.; Minard, Gayle; Maish, George O.; Dickerson, Roland N.
Purpose: We report a case of a patient with gastrointestinal dysmotility and substantial drainage losses who required parenteral nutrition (PN) and developed a non–anion gap metabolic acidosis secondary to a shortage of concurrent potassium acetate and sodium acetate PN additives. We describe how severe PN-associated metabolic consequences were averted during this acetate shortage.Summary: The patient with inability to swallow and significant weight loss was admitted to the hospital and given PN after failure to tolerate either gastric or jejunal feeding due to dysmotility and severe abdominal distension and discomfort. PN was initiated and the nasogastric and jejunal tubes were left to low intermittent suction or gravity drainage (average losses of 800 mL and 1600 mL daily, respectively) to reduce abdominal distension. The patient had been stable on PN for approximately 2 months prior to when a shortage in potassium acetate and sodium acetate occurred. As a result, potassium and sodium requirements had to be met with chloride and phosphate salts. The patient developed a non–anion gap metabolic acidosis after 11 days of acetate-free PN. Progression to severe acidemia was avoided by administration of sodium bicarbonate daily for 3 days and replacement of 0.9% sodium chloride supplemental intravenous fluid with lactated ringers solution.Conclusion: This case report illustrates that PN component shortages require clinicians to closely monitor patients who require PN. In addition, clinicians may need to use creative therapeutic strategies to avoid potential serious patient harm during PN component shortages.